Kecendrungan Nomophobia Ditinjau Dari Jenis Kelamin Pada Remaja Di Kota Bukittinggi - Pamungkas, Tri Bayu (Happiness: Journal of Psychology and Islamic Science, 2021)
Nomophobia is a new type of phobia that occurs as a result of rapid technological developments. This study aims to see the tendency of nomophobia among adolescents in the city of Bukittinggi. The subjects in this research were teenagers in the city of Bukittinggi, consisting of 80 men and 103 women. Data collection uses the Q-NMP scale (questionnaire nomophobia) with a 7-point liker scale model. The data analysis technique in this study used the independent sample t-test analysis technique. The results of the Independent Sample T-test difference, obtained a value of t = -, 450 with p = 0.566 (because the data is homogeneous, which is seen in the Equal Variences Assumed) there is no significant difference between the tendency of nomophobia in men and women. Keyword: Nomophobia, men, women ABSTRAK Nomophobia adalah phobia jenis baru yang terjadi akibat perkembangan teknologi yang semakin pesat. Penelitian ini bertujuan untuk melihat kecendrungan nomophobia pada remaja di Kota Bukittinggi. Subjek dalam penellitian ini merupakan remaja di Kota Bukittinggi yang terdiri dari 80 orang laki-laki dan 103 orang perempuan. Pengumpulan data menggunakan skala Q-NMP (quisioner nomophobia) dengan model skala liker 7 poin. Teknik analisis data dalam penelitian ini menggunakan teknik analisis independent sampel t-test. Hasil uji 91 beda Independent Sample T-test, diperoleh nilai t = -,450 dengan p= 0.566 (karena data homogen, yang dilihat adalah pada Equal Variences Assumed) tidak terdapat perbedaan yang signifikan antara kecenderungan nomophobia pada laki-laki dan perempuan